INFLUENCE OF HEALTH CARE SYSTEMS ON MODERN CONTRACEPTIVE UPTAKE AMONG WOMEN OF THE REPRODUCTIVE AGE IN TURKANA CENTRAL SUB-COUNTY, KENYA - Paul, Areman L.; Okenyoru, Douglas Sendora (International Journal of Engineering Technologies and Management Research, 2024)
Modern contraceptives, such as implants, coils, injections, and pills, are methods that interfere with normal ovulation and fertilization processes to prevent conception. These contraceptives play a crucial role in reproductive health and positively impact women’s well-being. However, there is global concern about their underutilization. It is against this background that this study sought to investigate the utilization of modern contraceptives among women of reproductive age in Turkana County. The specific objective of this study was to find out how health care system affects the access and utilization of modern contraceptives among women in Turkana Central Sub-County. The systematic sampling method was employed to select study participants, and quantitative data was collected through questionnaires. The Statistical Package for Social Sciences (SPSS) version 20.0 was used to analyze descriptive data and produce frequency tables, graphs, and pie charts. Chi-Square tests with a 95% confidence interval and a 0.05 margin of error were used to establish correlations between research variables. The findings of this study indicate that the healthcare system, such as accessibility to healthcare facilities, the availability of family planning services, healthcare workers’ attitudes, and service hours, were crucial in determining the use of contraceptives.